Modeling the Complex Systems of International Electronic Trade Financing Portfolio - Ya Li (2012 International Conference on Computer Science and Electronics Engineering, 2012)
How to help enterprises realize cost minimum and profits maximum, which is the goal of many foreign trade enterprises. Based on the theoretical basis and practical basis, this paper analyse international trade financing portfolio under cost constraints, for MK corporate case, raise the financing strategy of corresponding to the greast financing amounts under financing constraints.